(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article discusses the teachings of Feliks Koneczny about the nation and the state. Koneczny was an outstanding Polish historian, philosopher and historiosophist, and the author of many works devoted to the history of world civilizations. He described in his publications especially the Latin, Byzantine and Jewish civilizations. In his research focused on the issues of the nation and the state and their mutual relations. He believed that the existence of the nation is the result of the historical process taking place in the Latin civilization. No other civilization has enabled the emergence of a spiritual community that protects a person’s right to a dignified life. It enables the individual to develop comprehensive way, especially in the area of broadly understood spiritual culture. The state, on the other hand, is a community that organizes the nation for community life through efficient administration and governance that enables the realization of the aspirations of human beings. If the state pursues only the goals of the authorities, and not of the nation, it begins to be for a threat to him. The freedom of people in the state and respect for their dignity gives an opportunity development of national culture and strengthens the power of the state as a community of people, and not only physically coexisting individuals.